Penggunaan Fungsi Hitzl-Zele pada Implementasi Gabungan Secret Sharing Shamir’s (t, w)-Threshold Scheme dan Steganografi Audio Least Significant Bit (Jurnal EurekaMatika, 2025)
As information exchange becomes easier and faster through various media, ensuring information security has become increasingly difficult. To address the risks of information leakage and other threats, a combination of cryptography and steganography is employed. Shamir's (t, w)-Threshold Scheme in cryptography allows secret information to be divided into multiple parts, or shares, which are distributed among several key holders, so no single key holder possesses the entire information. Audio steganography using the Least Significant Bit (LSB) technique is applied to hide these shares in WAV audio files, utilizing the Hitzl-Zele function to determine the embedding locations within the audio data. This combination is implemented to an application built using Python, named “(t, w)-Threshold Scheme and LSB Hitzl-Zele.” The application demonstrates a good performance in maintaining information confidentiality, achieving a PSNR value of 112.43 decibels (dB).Keywords: Audio Steganography, Cryptography, Hitzl-Zele Function, Least Significant Bit, Secret Sharing Scheme.AbstrakSeiring dengan kemudahan dan kecepatan pertukaran informasi melalui berbagai media, keamanan informasi menjadi semakin sulit dikendalikan. Untuk mengatasi risiko kebocoran informasi dan ancaman lainnya, dilakukan kombinasi antara kriptografi dan steganografi. Kriptografi Shamir’s (t, w)-Threshold Scheme memungkinkan informasi rahasia dibagi menjadi beberapa bagian atau share yang didistribusikan kepada sejumlah pemegang kunci, sehingga tidak ada pemegang kunci tunggal. Steganografi audio dengan teknik Least Significant Bit (LSB) diterapkan untuk menyembunyikan share tersebut ke dalam file audio WAV, menggunakan fungsi Hitzl-Zele untuk menentukan lokasi penyematan dalam data audio. Kombinasi ini diimplementasikan pada aplikasi yang dibangun menggunakan Python, yang dinamakan “(t, w)-Threshold Scheme and LSB Hitzl-Zele”. Aplikasi ini menunjukkan performa yang baik dalam menjaga kerahasiaan informasi, dengan nilai PSNR sebesar 112,43 desibel (dB).
Keywords: Fungsi Hitzl-Zele; Kriptografi; Least Significant Bit; Skema Pembagian Rahasia; Steganografi Audio